Writing the Life of the Text: The Case of W.B. Yeats - Gould, Warwick (Miscelánea: A Journal of English and American Studies, 2004)
Using authors’ and publishers’ archives textual biography can trace multitudinous textual lives, afterlives and new lives in real incarnations. Those latter categories are whole subjects in themselves, and for other occasions: my examples in this paper are confined to the lives of certain texts during the lifetime of W. B. Yeats. My point of departure is Yeats’s well-known textual restlessness. He endlessly revised his work, and I was once inclined to see this as others had seen it, as evidence of a Darwinian process of aesthetic self-criticism, within the narrow focus of the work —the word, the line, the poem. At the core of such textual instability is authorial intention itself: in Yeats’s case the destabilising dream of finality, perfectionism, a collected works, an oeuvre, which he openly wanted from 1895 onwards. What might be labelled as the life of the text would lie beyond edited forms of it, in the history of books, in publishers’ archives such as Macmillan’s and in research collections of life documents and MSS. Every serious reader of Yeats engages at some level with that life of the text, which is why I am trying to write it. I find this process permits an intimate and sustainable recuperation of that concept so derided a few years ago: intention, a recoverable, mutating, demonstrable intention not foreclosed at, or by, the publication of the text. My argument, then, is a plea for the application of book historical methods to the construction of inner lives. It involves an accommodation of literary genetics and publishing history to single author bibliography.
Keywords: Yeats; Author's/publishers' archives; Textual biography; Oeuvre; Rewriting/revision; Textual instability; Authorial intention; Literary genetics; Publishing history; Author bibliography